Assessment of the patient satisfaction level with outpatient department services in a tertiary care hospital of Jammu region - Sharma, Rakesh K.; Gupta, Riya; Kapoor, Anuj; Zaffer, Imran; Hassan, Zahidul; Chalotra, Ritika; Singh, Amandeep; Gupta, Rajiv K. (International Journal Of Community Medicine And Public Health, 2023)
Background: Outpatient department (OPD) is that section of the hospital which is staffed and equipped to provide diagnostic, therapeutic and rehabilitative care to those patients who are not registered as inpatients while receiving the services during scheduled working hours. Objective of the study was to assess the patient satisfaction level with OPD services in a tertiary-care hospital of Jammu region. Methods: A cross-sectional study was conducted among patients visiting the OPD of the SMGS hospital GMC Jammu from January to March 2023. Exit interviews were conducted using a semi-structured questionnaire among patients availing the services from OPD. Results: Average percentage of total satisfaction score among sampled OPD patients has come out to be 68.13% whereas total average dissatisfaction score was 20.87% and the total average mild dissatisfaction score as 11.00%. Conclusions: This study suggests that patients were satisfied to a larger extent with OPD services except a few which are least satisfied especially with waiting time at registration counter.